DNA methylation signatures of alcohol use disorder: a large-scale meta-analysis in the Psychiatric Genomics Consortium - Zillich, Lea; D’Augello, Sofia; Avetyan, Diana; Delgado Gonzales de Kleber, Graciela; Gizer, Ian R.; Jung, Jeesun; Katrinli, Seyma; Kleber, Marcus E.; Merrill, Natalie; Moissl-Blanke, Angela P.; Núñez-Rios, Diana L.; Otto, Jacqueline M.; et al. (medRxiv, 2025)
Despite extensive research on DNA methylation (DNAm) signatures associated with alcohol use disorder (AUD), findings are often inconsistent and not replicated. We conducted a large-scale meta-analysis of epigenome-wide association studies (EWAS) to identify reliable, reproducible epigenetic markers of AUD. - Seven cohorts, comprising 3,775 individuals (1,325 with AUD), contributed to this meta-analysis within the framework of the Psychiatric Genomics Consortium Substance Use Disorders Epigenetics Working Group. Downstream analyses included the identification of differentially methylated regions, overrepresentation analyses, and the construction of a methylation risk score (MRS). - We identified 118 significant CpG sites associated with AUD, with the strongest association found at cg24889777 (p=5.12×10-17) in the long non-coding RNA LOC100505942. CpG sites were enriched for pathways related to GTPase signaling and transmembrane transporter activity, as well as EWAS signals of alcohol consumption. The MRS explained 10.44% of variance in heavy drinking in an independent cohort (N=2,534, AUC=0.657). - This large-scale meta-analysis offers key insights into the epigenetic mechanisms of AUD and lays the groundwork for future research on methylation risk scores for the diagnosis, prognosis, and treatment in AUD.
Gesehen am 12.11.2025